INFLUENCE OF BODY CONDITION SCORE AT THE TIME OF AI AND DURATION OF ESTRUS ON OVULATION RATE AND FERTILITY IN CROSSBRED JERSEY COWS - EZHILARASAN, C; MURUGAVEL, K; ANTOINE, D (The Indian Journal of Animal Reproduction, 2017)
Based on behavioural signs of estrus and on rectal palpation of genitalia, sixty-eight crossbred Jersey cows were selected to study the influence of Body Condition Score (BCS) at the time of AI and duration of estrus on ovulation rate and fertility. Ovarian Ultrasonography was carried out to determine the presence of preovulatory follicle (POF) on d0 (day of AI), and the disappearance of POF on d1 or d2 after AI, whichever is earlier. Ovulation was confirmed based on presence of CL on d12 post-AI on the ovary that had dominant follicle at the time of AI. Pregnancy diagnosis was done on d27 post-AI. Between pregnant and non-pregnant cows, BCS and duration of estrus were similar (p>0.05). Similarly, there was no correlation (p>0.05) between duration of estrus and intensity of estrus and between duration of estrus and BCS at the time of AI. A positive correlation was noticed between BCS and intensity of estrus. Also, BCS between group of cows that ovulated at different time intervals was similar (p>0.05). The duration of estrus was longer (p<0.05) in cows that ovulated beyond 48h after AI compared to other cows. The percentage of cow showing intense, intermediate and weak estrus signs was 63.1%, 36.8% and 0%, respectively. The ovulation and pregnancy rate tended to be higher (p>0.05) in cows that exhibited intense estrus compared to intermediate estrus